Nucleating agent as well as preparation method and application thereof

By loading zinc citrate on the surface of hydroxyapatite to form a nucleating agent with a core-shell structure, the problem of inorganic nucleating agents being unsatisfactory in polylactic acid is solved, and the crystallinity and heat resistance of polylactic acid are significantly improved.

CN119613812AActive Publication Date: 2025-03-14DONGHUA UNIV +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411847374.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-14
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing inorganic nucleating agents have poor effect on polylactic acid nucleation and poor compatibility, resulting in insufficient heat resistance of the products.

Method used

The nucleating agent with a core-shell structure is hydroxyapatite and the shell layer is zinc citrate. The zinc citrate is loaded on the surface of hydroxyapatite through the preparation method to improve its compatibility and dispersion with polylactic acid.

Benefits of technology

It significantly improves the crystallization rate and crystallinity of polylactic acid, improves heat resistance and stability in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613812A_ABST
    Figure CN119613812A_ABST
Patent Text Reader

Abstract

The invention discloses a nucleating agent as well as a preparation method and application thereof, belongs to the technical field of material engineering, and solves the problem that an inorganic nucleating agent in the prior art is not ideal in nucleating effect on polylactic acid. The nucleating agent is of a core-shell structure, a core layer is hydroxyapatite, and a shell layer is zinc citrate; the particle size of the nucleating agent is 1-2 [mu] m, and the particle size of the zinc citrate is 100-200 nm. According to the nucleating agent provided by the invention, the zinc citrate is loaded on the surface of the hydroxyapatite, so that the compatibility and dispersity of the zinc citrate and the polylactic acid are remarkably improved, and the crystallization rate and crystallinity of a polylactic acid system are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material engineering, and more specifically to a nucleating agent and a preparation method and application thereof. Background Art

[0002] Polylactic acid (PLA) is a new type of bio-based polymer, made from starch extracted from renewable plant resources (such as corn). Starch is saccharified to obtain glucose, which is fermented with specific bacteria to produce high-purity lactic acid, and then lactic acid is synthesized into polylactic acid. Polylactic acid is a new type of bio-based material with good biodegradability, biocompatibility and processing performance.

[0003] Polylactic acid is a semi-crystalline polymer with a slow crystallization rate. Therefore, the heat resistance of the products made from it is poor, and the heat deformation temperature (HDT) is ~58°C, which seriously hinders the application of polylactic acid in a wider range of fields. After the amorphous polylactic acid is completely crystallized, the bending modulus and strength increase by 25%, and the impact resistance increases. In order to improve the heat resistance of polylactic acid, scientific researchers have done a lot of research. Patent CN103146163A discloses a high-efficiency nucleating agent of organic-inorganic hybridization of sepiolite with diisocyanate and maleimide, which can increase the crystallinity of the product to 55%, shorten the molding time of polylactic acid products and increase the heat resistance temperature of the product to above 120°C. Patent CN115044069A discloses a preparation method of polylactic acid mixed with phenylphosphonate, which has good compatibility with the polylactic acid matrix and can shorten the synthesis time of the polylactic acid nucleating agent. Patent CN110713583A discloses a method for preparing an in-situ synthesized polylactic acid nucleating agent, in which diisocyanate and hydrazide are added to the polylactic acid melt for in-situ reaction grafting, which significantly improves the heat resistance and toughness of the polylactic acid. Patent CN108384210A discloses a method for improving polylactic acid using pyruvate as a polylactic acid nucleating agent, which can effectively improve the crystallization rate and crystallinity of polylactic acid, and also has potential biocompatibility and degradability.

[0004] Adding nucleating agents for heterogeneous nucleation is the most effective and economical way to crystallize and heat-resistant polymers. Organic nucleating agents have good nucleation effects, but they often contain aromatic structures and even heavy metal ions, which can cause certain harm to the human body and the environment. Inorganic nucleating agents usually include talcum powder, montmorillonite, carbon black, apatite, etc., which are widely available and inexpensive, and are therefore widely used in the field of polylactic acid nucleation. However, this type of nucleating agent has a poor nucleation effect. When added in small amounts, the nucleation effect is not obvious. When the content is high, the product is prone to become brittle, affecting the use effect. Therefore, how to improve the compatibility of inorganic nucleating agents with polylactic acid matrix and improve the nucleation effect is an urgent problem to be solved. Summary of the invention

[0005] The invention provides a nucleating agent and a preparation method and application thereof, which are used to solve the problem in the prior art that the inorganic nucleating agent has an unsatisfactory nucleating effect on polylactic acid.

[0006] In a first aspect, the present invention provides a nucleating agent having a core-shell structure, wherein the core layer is hydroxyapatite and the shell layer is zinc citrate; the particle size of the nucleating agent is 1 to 2 μm, and the particle size of the zinc citrate is 100 to 200 nm.

[0007] In a second aspect, the present invention provides a method for preparing a nucleating agent, comprising the following steps: adding a metal chelating agent to a uniform turbid solution of hydroxyapatite, heating to 70-90°C; adding a zinc ion solution, maintaining the temperature for 50-90 minutes, adding an alkaline solution and reacting for 20-40 minutes; adding a citric acid solution, reacting for 1.5-2.5 hours to obtain a crude product; and obtaining the nucleating agent after purification.

[0008] As a possible implementation method, the purification includes the following steps: allowing the crude product to stand for 10 to 15 hours, centrifuging, and drying to obtain the nucleating agent.

[0009] As a possible implementation, the centrifugal conditions are: a rotation speed of 6000-10000 r / m, and a duration of 5-10 min; and / or, the drying conditions are: vacuum drying at 50-80° C. for 20-30 h.

[0010] As a possible implementation, the uniform turbid solution of hydroxyapatite is obtained by uniformly dispersing hydroxyapatite in deionized water by ultrasonication; and / or, the adding of alkaline solution is performed dropwise; and / or, the adding of citric acid solution is performed dropwise.

[0011] As a possible implementation manner, the molar ratio of the hydroxyapatite, the zinc ions and the citric acid is 1:5-20:10-40; and / or the mass ratio of the metal chelator and the hydroxyapatite is 0.3-0.4:1; and / or the concentration of the alkaline solution is 1-2 mol / L, and the molar ratio of the alkali to the zinc ions is 1:0.2-1; and / or the concentration of the citric acid solution is 1.5-2.5 mol / L, and the molar ratio of the citric acid to the zinc ions is 1:0.3-0.7.

[0012] As a possible implementation, the metal chelator is any one of ethylenediaminetetraacetic acid, aminotriacetic acid, and diethylenetriaminepentaacetic acid; and / or the zinc ion is any one of zinc sulfate solution and zinc nitrate solution; and / or the alkaline solution is any one of sodium hydroxide solution and potassium hydroxide solution.

[0013] In a third aspect, the present invention provides a use of the nucleating agent described in any possible implementation of the first aspect or the nucleating agent prepared by the preparation method described in any possible implementation of the second aspect in the preparation of polylactic acid products.

[0014] As a possible implementation, the nucleating agent is used in combination with a chain extender.

[0015] As a possible implementation, the polylactic acid product is applied in a specific environment; the specific environment is a temperature of 25 to 130° C. and a humidity of 65% to 100%; or the specific environment is a temperature of 25 to 130° C. and immersed in water.

[0016] The nucleating agent provided by the present invention loads zinc citrate on the surface of hydroxyapatite. There are a large number of hydroxyl groups on the surface of hydroxyapatite, which is hydrophilic, while polylactic acid is a hydrophobic polymer. After the surface of hydroxyapatite is loaded with zinc citrate, the hydrophilicity is reduced, and at the same time, the lattice matching relationship between zinc citrate and polylactic acid can induce the stacking of polylactic acid molecular chains, thereby improving the compatibility and dispersibility of the two and increasing the crystallinity. The nucleating agent provided by the present invention significantly improves its compatibility and dispersibility with polylactic acid, and effectively increases the crystallization rate and crystallinity of the polylactic acid system.

[0017] The preparation method of the nucleating agent provided by the present invention has the advantages of simple operation, small dosage and low cost.

[0018] The nucleating agent provided by the present invention, when used as a polylactic acid nucleating agent and in combination with a chain extender, has the effect of simultaneously improving the heat resistance of polylactic acid and increasing the melt strength of polylactic acid. The injection molded sample can be used under high temperature and high humidity conditions without deformation, and has excellent extreme condition stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1The synthetic route of the nucleating agent provided in the embodiment of the present invention, wherein chelating means chelation, absorption means absorption, complexation means complexation, HAP means hydroxyapatite, and ZnCC@HAP means zinc citrate loaded on hydroxyapatite, i.e. the nucleating agent prepared by the present invention.

[0021] Figure 2 TEM images of different stages of the preparation process of the nucleating agent B provided in an embodiment of the present invention, wherein a) represents zinc citrate, nucleating agent A (ZnCC); (b), (c), and (d) represent hydroxyapatite-loaded zinc citrate, nucleating agent B (ZnCC@HAP-1.0), nucleating agent C (ZnCC@HAP-1.5), and nucleating agent D (ZnCC@HAP-2.0), respectively.

[0022] Figure 3 The thermogravimetric curve provided by the embodiment of the present invention, wherein HAP is hydroxyapatite (nucleating agent E), ZnCC@HAP-1.0, ZnCC@HAP-1.5 and ZnCC@HAP-2.0 are nucleating agent B, nucleating agent C and nucleating agent D respectively.

[0023] Figure 4 The XPS provided by the embodiment of the present invention, wherein HAP is hydroxyapatite (nucleating agent E), ZnCC@HAP-1.0, ZnCC@HAP-1.5 and ZnCC@HAP-2.0 are nucleating agent B, nucleating agent C and nucleating agent D respectively.

[0024] Figure 5 FTIR provided by an embodiment of the present invention, wherein HAP is hydroxyapatite (nucleating agent E), ZnCC, ZnCC@HAP-1.0, ZnCC@HAP-1.5 and ZnCC@HAP-2.0 are nucleating agent A, nucleating agent B, nucleating agent C and nucleating agent D, respectively.

[0025] Figure 6 XRD images provided for the embodiments of the present invention, HAP is hydroxyapatite (nucleating agent E), ZnCC, ZnCC@HAP-1.0, ZnCC@HAP-1.5 and ZnCC@HAP-2.0 are nucleating agent A, nucleating agent B, nucleating agent C and nucleating agent D respectively

[0026] Figure 7Schematic diagram of chloroform dispersion solution provided in an embodiment of the present invention, from left to right: chloroform, HAP / chloroform (chloroform solution of nucleating agent E), ZnCC@HAP-1.0 / chloroform (chloroform solution of nucleating agent B), ZnCC@HAP-1.5 / chloroform (chloroform solution of nucleating agent C), ZnCC@HAP-2.0 / chloroform (chloroform solution of nucleating agent D) and ZnCC / chloroform (chloroform solution of nucleating agent A). DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In order to solve the problem in the prior art that the nucleation effect of inorganic nucleating agents on polylactic acid is not ideal, an embodiment of the present invention provides a preparation experiment of a nucleating agent. It can be seen that the product prepared by the present invention has a rod-like morphology, which is beneficial to inducing crystallization and orientation of the polymer during the spinning process, thereby improving the performance of the fiber.

[0029] Furthermore, an embodiment of the present invention provides an application effect test experiment of a nucleating agent. It can be seen that the polylactic acid product prepared by the product prepared by the present invention has high stability in extreme environments and can adapt to high temperature and high humidity environments.

[0030] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0031] Example 1

[0032] This embodiment provides a preparation experiment of a nucleating agent.

[0033] In this embodiment, the nucleating agents B to D are Figure 1 The synthetic route shown was used for preparation.

[0034] Dissolve 3g zinc acetate in 90mL ethanol, then add 3mL distilled water. Heat the solution to 80℃, stir and reflux for 2h, add equimolar (2.6257g) citric acid (dissolved in ethanol, 2mol / L) after stirring, react for 5h, cool naturally to room temperature, and stand overnight to improve crystallinity. The precipitate is filtered, the filter cake is repeatedly washed with ethanol and distilled water three times, and a white powder is obtained after vacuum drying; it is dried at 120℃ for 5h to obtain zinc citrate (ZnCC) as nucleating agent A.

[0035] 2 g of hydroxyapatite was placed in 100 mL of deionized water and stirred for 30 min by ultrasonic dispersion; 0.68 g of metal chelator was added, heated to 80 ° C in a water bath, and stirred for 3 hours; the temperature was maintained at 80 ° C, 0.04 mol of zinc sulfate was added, and the reaction was carried out for 1 hour; 16 mL of 1.5 mol / L sodium hydroxide solution was added dropwise, and the reaction was carried out for 0.5 hours after the addition was completed; 40 mL of 2 mol / L citric acid solution was added dropwise, and the reaction was carried out for 2 hours; it was allowed to stand for 12 hours; differential centrifugation was performed for 8 minutes at a speed of 8000 r / m; the supernatant was removed, and the mixture was dried at 60 ° C in a vacuum oven for 24 hours to obtain ZnCC@HAP-1.0, i.e., nucleating agent B.

[0036] 2 g of hydroxyapatite was placed in 100 mL of deionized water and stirred for 30 min by ultrasonic dispersion; 0.68 g of metal chelator was added, heated to 80 ° C in a water bath, and stirred for 3 hours; the temperature was maintained at 80 ° C, 0.06 mol of zinc sulfate was added, and the reaction was carried out for 1 hour; 24 mL of 1.5 mol / L sodium hydroxide solution was added dropwise, and the reaction was carried out for 0.5 hours after the addition was completed; 60 mL of 2 mol / L citric acid solution was added dropwise, and the reaction was carried out for 2 hours; it was allowed to stand for 12 hours; differential centrifugation was performed for 8 minutes at a speed of 8000 r / m; the supernatant was removed, and the mixture was dried in a vacuum oven at 60 ° C for 24 hours to obtain ZnCC@HAP-1.5, i.e., nucleating agent C.

[0037] 2 g of hydroxyapatite was placed in 100 mL of deionized water and stirred for 30 min by ultrasonic dispersion; 0.68 g of metal chelator was added, heated to 80 ° C in a water bath, and stirred for 3 hours; the temperature was maintained at 80 ° C, 0.08 mol of zinc sulfate was added, and the reaction was carried out for 1 hour; 32 mL of 1.5 mol / L sodium hydroxide solution was added dropwise, and the reaction was carried out for 0.5 hour after the addition was completed; 80 mL of 2 mol / L citric acid solution was added dropwise, and the reaction was carried out for 2 hours; it was allowed to stand for 12 hours; differential centrifugation was performed for 8 minutes at a speed of 8000 r / m; the supernatant was removed, and the mixture was dried at 60 ° C in a vacuum oven for 24 hours to obtain ZnCC@HAP-2.0, i.e., nucleating agent D.

[0038] As nucleating agent E, 2 g of hydroxyapatite was used.

[0039] Example 2

[0040] This embodiment provides a performance characterization experiment of a nucleating agent.

[0041] The nucleating agents B to E prepared in Example 1 were observed by TEM, and the following results were obtained: Figure 2 The results shown, Figure 2 Comparing (b), (c), and (d) with (a), the large rod-shaped object is hydroxyapatite, and the small black-gray particles on the surface are zinc citrate. It can be seen that the target product was successfully prepared.

[0042] The nucleating agents B to E prepared in Example 1 were subjected to thermogravimetric analysis. The analysis conditions were as follows: 3 to 5 mg of the sample was weighed in an Al2O3 crucible under a nitrogen atmosphere and heated from 30°C to 600°C at a heating rate of 10°C to obtain the following: Figure 3 The results shown by Figure 3 It can be seen that with the increase of zinc citrate in the synthesis ratio, the thermal weight loss of the material becomes obvious. Combined with the thermogravimetric curve of zinc citrate, it can be concluded that the loading amount of zinc citrate increases and the material is successfully loaded on the surface of hydroxyapatite.

[0043] The nucleating agents B to E prepared in Example 1 were subjected to X-ray photoelectric spectroscopy analysis, and the XPS spectra were collected using a monochromatic Al Kα source, and the following results were obtained: Figure 4 The spectrum shown is Figure 4 It can be seen that with the increase of zinc citrate in the synthesis ratio, the signal peak of the Zn element is also enhanced accordingly, indicating that ZnCC is successfully loaded on the surface of hydroxyapatite.

[0044] The nucleating agents A to E prepared in Example 1 were subjected to infrared spectroscopy analysis. The test conditions were as follows: the corresponding nucleating agents were ground with potassium bromide and then tested. The projection mode was selected and the scanning wave number range was 4000-600 cm -1 , resolution 4cm -1 , the number of scans is 32, and the result is Figure 5 The results shown by Figure 5 It can be seen that the corresponding Zn-O bond can be observed on the surfaces of nucleating agents B, C, and D at 637 cm -1 The absorption peaks near the -COO bond are at 1559 cm -1 The absorption peak near , proved that zinc citrate nanoparticles were successfully loaded on the hydroxyapatite surface.

[0045] The nucleating agents A to E prepared in Example 1 were subjected to X-ray diffraction (XRD) testing. The testing conditions were: a Cu-Kα target and an X-ray wavelength of The test voltage and current were 40 kV and 40 mA respectively, the scanning angle range was 5° to 70°, the step size was 0.02°, and the scanning rate was 0.25° / s. Figure 6 The results are shown in Figure 2, where ZnCC represents zinc citrate (nucleating agent A); HAP represents hydroxyapatite (nucleating agent E); ZnCC@HAP-1.0, ZnCC@HAP-1.5, and ZnCC@HAP-2.0 represent nucleating agents B, C, and D, respectively. Figure 6It can be seen that the diffraction peaks of ZnCC appear in nucleating agents B, C and D, among which the absorption peak at 2θ=12.1 corresponds to the 020 crystal plane of ZnCC. With the increase of feed ratio, the peak intensity of nucleating agents B, C and D gradually increases, indicating that the amount of zinc citrate grafted on the surface of hydroxyapatite gradually increases.

[0046] The nucleating agents A to E prepared in Example 1 were tested for dispersibility. The testing conditions were as follows: 0.1 g of the nucleating agent was dissolved in 10 mL of chloroform solution and ultrasonically dispersed for 1 h to obtain the following: Figure 7 The results shown by Figure 7 It can be seen that the dispersibility of hydroxyapatite in chloroform is poor and the solution is very turbid. With the loading of zinc citrate, it can be seen that the hydroxyapatite solution becomes clearer, indicating that the dispersibility of the material in chloroform becomes better, indicating that the compatibility of polylactic acid and the nucleating agent is improved.

[0047] Example 3

[0048] This embodiment provides an application effect test experiment of a nucleating agent.

[0049] 10 g of the nucleating agent to be tested was added to 1000 g of polylactic acid (PLA), and preliminary solid phase mixing was performed. The mixture was melt-mixed and granulated by a twin-screw extruder. After drying, the mixture was injection molded (mold temperature was 90°C) to obtain a polylactic acid product. The product was soaked in water at 95°C and 110°C for 30 min, respectively, and heated in ovens at 60°C, 100°C and 130°C, respectively, and the morphological differences were recorded to test the stability.

[0050] In this example, the nucleating agents B to E prepared in Example 1 were used as the nucleating agents to be tested, and their respective stabilities were tested to obtain the results shown in Table 1.

[0051] Table 1 Product stability under different test environments

[0052] 95℃ water 110℃ water 60℃ oven 100℃ oven 130℃ oven Nucleating Agent B Invisible Change Invisible Change Invisible Change Invisible Change Invisible Change Nucleating agent C Invisible Change Invisible Change Invisible Change Invisible Change Invisible Change Nucleating agent D Invisible Change Invisible Change Invisible Change Invisible Change Invisible Change Nucleating agent E Slight deformation Slight deformation Slight deformation Slight deformation Moderate deformation

[0053] As can be seen from Table 1, the polylactic acid products prepared by the present invention with the participation of nucleating agents B to D have high stability in extreme environments. After the polylactic acid is added with the nucleating agent, it will induce the polylactic acid to form a large number of crystal nuclei, and the crystallization rate will be accelerated, thereby greatly improving the crystallinity of the material, reducing the amorphous area, and hindering the movement of the chain, thereby improving the heat resistance of the material.

[0054] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0055] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A nucleating agent, characterized in that It is a core-shell structure, in which the core layer is hydroxyapatite and the shell layer is zinc citrate; The particle size of the nucleating agent is 1-2 μm, and the particle size of the zinc citrate is 100-200 nm.

2. A method for preparing a nucleating agent, characterized in that: The following steps are involved: Add the metal chelating agent to the uniform turbid solution of hydroxyapatite and heat it to 70-90°C; Add zinc ion solution, maintain the temperature for 50 to 90 minutes, and react for 20 to 40 minutes after adding alkali solution; Add citric acid solution and react for 1.5 to 2.5 hours to obtain a crude product; The nucleating agent is obtained after purification.

3. The preparation method according to claim 2, characterized in that: The purification comprises the following steps: The crude product is allowed to stand for 10 to 15 hours, centrifuged and dried to obtain the nucleating agent.

4. The preparation method according to claim 3, characterized in that: The centrifugal conditions are: a rotation speed of 6000-10000 r / m and a duration of 5-10 min; And / or, the drying condition is: vacuum drying at 50-80° C. for 20-30 hours.

5. The preparation method according to claim 2, characterized in that: The uniform turbid solution of hydroxyapatite is obtained by uniformly dispersing hydroxyapatite in deionized water by ultrasonication; And / or, the adding of the alkaline solution is done dropwise; And / or, the citric acid solution is added dropwise.

6. The preparation method according to claim 2, characterized in that: The molar ratio of the hydroxyapatite, the zinc ion and the citric acid is 1:5-20:10-40; and / or, the mass ratio of the metal chelating agent to the hydroxyapatite is 0.3-0.4:1; And / or, the concentration of the alkaline solution is 1-2 mol / L, and the molar ratio of the alkali to the zinc ion is 1:0.2-1; And / or, the concentration of the citric acid solution is 1.5-2.5 mol / L, and the molar ratio of the citric acid to the zinc ions is 1:0.3-0.

7.

7. The preparation method according to claim 2, characterized in that: The metal chelating agent is any one of ethylenediaminetetraacetic acid, aminotriacetic acid, and diethylenetriaminepentaacetic acid; And / or, the zinc ion is any one of a zinc sulfate solution and a zinc nitrate solution; And / or, the alkaline solution is any one of a sodium hydroxide solution and a potassium hydroxide solution.

8. Use of the nucleating agent according to claim 1 or the nucleating agent prepared by the preparation method according to any one of claims 2 to 7 in the preparation of polylactic acid products.

9. The use according to claim 8, characterized in that: The nucleating agent is used in combination with a chain extender.

10. The use according to claim 8, characterized in that: The polylactic acid product is used in a specific environment; The specific environment is a temperature of 25 to 130° C. and a humidity of 65% to 100%; or the specific environment is a temperature of 25 to 130° C. and soaking in water.

Citation Information

Patent Citations

  • Preparation method of polylactic acid nucleating agent

    CN103146163A

  • Application of acetonates and modified polylactic acid

    CN108384210A

  • In-situ synthesis method of polylactic acid nucleating agent

    CN110713583A

  • Preparation method of phenyl phosphonate-doped polylactic acid

    CN115044069A

  • Calcium-carbonate-supported nucleating agent used for poly(lactic acid) crystallization and preparation method thereof

    CN102212257A